Multiparametric optical characterization of airborne dust with single particle extinction and scattering. Issue 4 (2nd April 2020) - Cremonesi, Llorenç; Passerini, Andrea; Tettamanti, Agostino; Paroli, Bruno; Delmonte, Barbara; Albani, Samuel; Cavaliere, Francesco; Viganò, Daniele; Bettega, Giovanni; Sanvito, Tiziano; Pullia, Alberto; Potenza, Marco A. C.
Abstract: We describe a robust, portable, deployable instrument for multiparametric optical characterization of single airborne particles. It is based on the Single Particle Extinction and Scattering method with additional sensors at 45° and 90° angles. Four independent optical parameters are associated to each particle. Basically, it provides a rigorous measurement of the extinction cross section and the complex amplitude of the forward scattered field. Moreover, thanks to the multiparametric single particle approach, it is possible to roughly classify the particles within a size range from a few hundreds of nanometers to some micrometers. By assigning a reasonable single scattering albedo for each population, our data are enough to fit the phase function with acceptable uncertainties. We report here the results of tests performed with water droplets, generating well controlled data without any free parameters. Data analysis is described in detail. We also report measurements performed on urban aerosol collected in the city of Milan by recovering the optical properties and feeding radiative transfer models. The findings reported here support the importance of an accurate measurement of the phase function, as already established by the Community. Copyright © 2020 American Association for Aerosol Research